Sistem Informasi Manajemen Audit Trio Motor Banjarmasin (Studi Kasus : General Affair) - fahmi, syahril; Regyta Cahyani, Malika (Journal Information Technology Trends (JITRENDS), 2023)
The study discusses the development of the Audit Management Information System (SIMA) at PT. Trio Motor, a company selling cars and motorcycles, also serving as the Main Dealer for Honda motorcycles in South Kalimantan and Central Kalimantan. SIMA addresses branch separation and reduces fraud in audits. Its goal is to streamline data collection, storage, analysis, and enhance planning, execution, and reporting efficiency. The research formulates design, creation, and implementation issues of SIMA for spare part audits. SIMA scans real-time part numbers, shelf locations, generates H3 format reports, and conducts synchronized warehouse audits. It aims to design, create, and utilize SIMA as a spare parts audit tool. The benefit lies in improving spare parts stock opname data collection. SIMA uses UML for database design, SQLServer for storage, and is developed with codeigniter 3 and bootstrap. It offers user access levels: Super Admin, Auditor Manager, Auditor, General Affairs, and Warehouse. Recommendations suggest ongoing development for complexity, features, and regular maintenance to prevent bugs. This research is crucial in aiding PT. Trio Motor's Audit Division for efficient and effective spare parts audits, reducing fraud risk.